Lysyl oxidase‐like 2 is critical to tumor microenvironment and metastatic niche formation in hepatocellular carcinoma - Wong, Carmen Chak‐Lui; Tse, Aki Pui‐Wah; Huang, Yan‐Ping; Zhu, Yan‐Ting; Chiu, David Kung‐Chun; Lai, Robin Kit‐Ho; Au, Sandy Leung‐Kuen; Kai, Alan Ka‐Lun; Lee, Joyce Man‐Fong; Wei, Larry Lai; Tsang, Felice Ho‐Ching; Lo, Regina Cheuk‐Lam; et al. (Hepatology (Baltimore, Md.), 2014)
Poor prognosis of cancers, including hepatocellular carcinoma (HCC), is mainly associated with metastasis; however, the underlying mechanisms remain poorly understood. This article investigates the role of lysyl oxidase‐like 2 (LOXL‐2) in the biology of HCC metastasis. First, we showed that HCC metastasis relies on a collagen‐modifying enzyme, LOXL2, which was significantly overexpressed in tumorous tissues and sera of HCC patients, indicating that LOXL2 may be a good diagnostic marker for HCC patients. Second, we delineated a complex, interlinked signaling network that involves multiple regulators, including hypoxia, transforming growth factor beta (TGF‐β), and microRNAs (miRNAs), converging to control the expression of LOXL2. We found not only that LOXL2 was regulated by hypoxia/hypoxia‐inducible factor 1 alpha (HIF‐1α), but also that TGF‐β activated LOXL2 transcription through mothers against decapentaplegic homolog 4 (Smad4), whereas two frequently underexpressed miRNA families, miR‐26 and miR‐29, cooperatively suppressed LOXL2 transcription through interacting with the 3' untranslated region of LOXL2. Third, we demonstrated the imperative roles of LOXL2 in modifying the extracellular matrix components in the tumor microenvironment and metastatic niche of HCC. LOXL2 promoted intrahepatic metastasis by increasing tissue stiffness, thereby enhancing the cytoskeletal reorganization of HCC cells. Furthermore, LOXL2 facilitated extrahepatic metastasis by enhancing recruitment of bone‐marrow–derived cells to the metastatic site. Conclusion: These findings integrate the clinical relevance, molecular regulation, and functional implications of LOXL2 in HCC metastasis. (Hepatology 2014;60:1645–1658)